Income taxation versus mangerial decisions - Tomasz Wołowiec; Tomasz Skica; Anna Nedyalkova (e-Finanse: Financial Internet Quarterly, 2014)
Taking rational decisions in a company, both current and strategic, requires knowing and taking into consideration the external conditions of the conducted activity. The accuracy of decisions made, as well as the ability to adjust to a changing external environment determines not only the effectiveness of the enterprise's operations, but also its ability to conduct further activity. The paper aims at demonstrating the influence of income tax on the activity of economic entities and also on the decisions taken by management. The article is composed of three complementary sections. The first one - the introduction - is an attempt at outlining the subject framework for the article and demonstrating potential areas in which the tax system affects the economy and the associated consequences. The second part provides an empirical analysis presenting possible variants (simulations) of declaring income and related management decisions taken in various time horizons and boundary conditions, reflecting the criteria of a resident. The third part of the paper comprises conclusions based on the results of conducted simulations, related to the influence of the income tax construction on financial decisions taken by enterprises and related consequences.
Keywords: H21; H24; H30; E62; F43; 330; taxation; market reaction; managerial decisions; effect of taxes